3D collage: expressive non-realistic modeling - Gal, Ran; Sorkine, Olga; Popa, Tiberiu; Sheffer, Alla; Cohen-Or, Daniel (NPAR '07 Proceedings of the 5th international symposium on Non-photorealistic animation and rendering, 2007)
The ability of computer graphics to represent images symbolically has so far been used mostly to render existing models with greater clarity or with greater visual appeal. In this work, we present a method aimed at harnessing this symbolic representation power to increase the expressiveness of the 3D models themselves. We achieve this through modification of the actual representation of 3D shapes rather than their images. In particular, we focus on 3D collage creation, namely, a generation of compound representations of objects. The ability of such representations to convey multiple meanings has been recognized for centuries. At the same time, it has also been acknowledged that for humans, the creation of compound 3D shapes is extremely taxing. Thus, this expressive but technically challenging artistic medium is a particularly good candidate to address using computer graphics methods. We present an algorithm for 3D collage generation that serves as an artistic tool performing the challenging 3D processing tasks, thus enabling the artist to focus on the creative side of the process.